Effects of depression and anxiety on mortality in a mixed cancer group: a longitudinal approach using standardised diagnostic interviews. Issue 6 (23rd October 2014) - Chan, Caryn Mei Hsien; Wan Ahmad, Wan Azman; MD Yusof, Mastura; Ho, Gwo‐Fuang; Krupat, Edward
Abstract Background Distress and psychiatric morbidity in cancer patients are associated with poorer outcomes including mortality. In this study, we examined the prevalence of psychiatric morbidity and its association with cancer survival over time. Methods Participants were 467 consecutive adult cancer patients attending oncology follow‐ups at a single academic medical centre. Assessment consisted of the Hospital Anxiety and Depression Scale and Structured Clinical Interview for Diagnostic and Statistical Manual of Mental Disorders, 4th edition, text revision. Comparison between co‐morbid psychiatric cases and non‐cases was made in follow‐ups of up to 24 months. Results Of the 467 patients, 217 of 220 patients with elevated total Hospital Anxiety and Depression Scale scores (≥16) met the criteria for an Axis I disorder at 6 months follow‐up, with 102 of the follow‐up sample having a persistent diagnosable psychiatric disorder after 1 year. The most frequent initial diagnoses were minor depression (17.6%), major depressive disorder (15.8%) and adjustment disorder (15.8%). Cancer patients without psychiatric morbidity had a survival benefit of 2.24 months or 67 days. Mean survival at 24 months was 20.87 months (95% CI 20.06–21.69) for cancer patients with psychiatric morbidity versus 23.11 months (95% CI 22.78–23.43) for those without (p < 0.001 for log rank). After adjusting for demographics and cancer stage on a Cox proportional hazards model, psychiatric morbidity remained associated with worse survival (hazard ratio 4.13, 95% CI 1.32–12.92, p = 0.015). Conclusions This study contributes to the growing body of evidence linking psychiatric morbidity to cancer mortality. Treating underlying psychiatric conditions in cancer may therefore improve not just quality of life but also survival. Copyright © 2014 John Wiley & Sons, Ltd.